Prognostic significance of CD45RO+ memory T cells in renal cell carcinoma - Hotta, K (Nature Publishing Group, 2011)
BACKGROUND: Memory T cells are well known to have a critical role for host defense in humans. However, their role in actual human cancer remains largely unknown. In this study, we tried to reveal the clinical importance of tumour-infiltrating CD45RO+ memory T cells in renal cell carcinoma (RCC). METHODS: We analysed 105 patients with RCC, who received radical or partial nephrectomy. Those were 65 in TNM stage I, 7 in stage II, 15 in stage III, and 18 in stage IV, respectively. CD45RO expression was evaluated by immunohistochemistry. CD4 and CD8 expressions were also systematically assessed in the same manner. RESULTS: Patients with higher TNM stage or high nuclear grade were found to have higher densities of CD45RO. Furthermore, CD45RO status was positively correlated with preoperative C-reactive protein level. In prognostic analysis, CD45RO+lo patients had a significantly better prognosis than CD45RO+hi patients. There was also a significant difference between CD4+lo and CD4+hi groups, whereas no significant difference was observed in CD8 T-cell status. Finally, multivariate analysis revealed that CD45RO+ status was the independent prognostic factor for patient overall survival. CONCLUSION: CD45RO+ memory T-cell status has a significant independent prognostic value, indicating that the adaptive immune response is functionally critical in human RCC.